2016
DOI: 10.15298/rusjtheriol.15.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Early Middle Pleistocene Ellobius (Rodentia, Cricetidae, Arvicolinae) from Armenia

Abstract: Early Pliocene) radiation of Arvicolinae (Abramson et al., 2009a, b). Therefore, most specific features of mole voles developed due to a strong burrowing specialization (incisor digging, molar enamel thickening and partial reduction of molars) so that Early Pleistocene forms still show much more arvicoline-looking molars with some mimomyoid characters (e.g. Mimomys-ridge and relics of enamel islets). As with many rapidly evolving arvicoline phylums, molar evolution in mole voles shows a progressive hypsodonty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…Previously, Maul et al (2015) considered the AC shape as a discriminant criteria, being broad in Ellobius lutescens, narrow in Ellobius talpinus and elongated in Ellobius fuscocapillus. Tesakov (2016) found that the size of E. lutescens is slightly smaller than E. fuscocapillus. Rey-Rodríguez et al (2020) reported that the confluence between T4 and T5 differs among the species, with T1-T2 and T3-T4 being slightly less pairwise opposed in E. lutescens.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Previously, Maul et al (2015) considered the AC shape as a discriminant criteria, being broad in Ellobius lutescens, narrow in Ellobius talpinus and elongated in Ellobius fuscocapillus. Tesakov (2016) found that the size of E. lutescens is slightly smaller than E. fuscocapillus. Rey-Rodríguez et al (2020) reported that the confluence between T4 and T5 differs among the species, with T1-T2 and T3-T4 being slightly less pairwise opposed in E. lutescens.…”
Section: Discussionmentioning
confidence: 92%
“…Ellobius lutescens (western mole vole) is distributed in northwestern Iran, Iraq, Azerbaijan, Armenia and eastern Anatolia (Thomas, 1905;Ellerman and Morrison-Scott, 1951;Darlington, 1957;Osborn, 1962;Walker, 1964;Lay, 1967;Hassinger, 1973;Roberts, 1977;Corbet, 1978;Corbet and Hill, 1991;Coşkun, 1997;Nowak, 1999;Wilson and Reeder, 2005;Kryštufek and Shenbrot, 2016;Wilson et al, 2017). In Iran, this species is found in mountain grasslands, sandy semi-deserts and steppe areas (Kryštufek and Shenbrot, 2016;Tesakov, 2016).…”
Section: Distribution and Ecological Remarks Of The Extant Ellobius Smentioning
confidence: 99%
See 3 more Smart Citations